2013
DOI: 10.1016/j.bbrc.2013.04.070
|View full text |Cite
|
Sign up to set email alerts
|

Acoustical sensing of cardiomyocyte cluster beating

Abstract: Spontaneously beating human pluripotent stem cell-derived cardiomyocytes clusters (CMCs) represent an excellent in vitro tool for studies of human cardiomyocyte function and for pharmacological cardiac safety assessment. Such testing typically requires highly trained operators, precision plating, or large cell quantities, and there is a demand for real-time, label-free monitoring of small cell quantities, especially rare cells and tissue-like structures. Array formats based on sensing of electrical or optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The QCM has been also successfully applied to study cell adhesion, the surface spreading of living cells, the interaction of antibody with growth factor receptors of cancer cells, and cell responses when exposed to nanoparticles and nanotubes . Tymchenko et al used the QCM with dissipation monitoring (QCM‐D) biosensor setup to study the biomechanical properties of stem cell CM clusters. This label‐free technology allows the monitoring of changes in mass and viscoelastic properties of surface‐adhered CMs in real time, with a sampling frequency of 10 Hz.…”
Section: Methods Results and Discussionmentioning
confidence: 99%
“…The QCM has been also successfully applied to study cell adhesion, the surface spreading of living cells, the interaction of antibody with growth factor receptors of cancer cells, and cell responses when exposed to nanoparticles and nanotubes . Tymchenko et al used the QCM with dissipation monitoring (QCM‐D) biosensor setup to study the biomechanical properties of stem cell CM clusters. This label‐free technology allows the monitoring of changes in mass and viscoelastic properties of surface‐adhered CMs in real time, with a sampling frequency of 10 Hz.…”
Section: Methods Results and Discussionmentioning
confidence: 99%
“…It is interesting to note that the shape of the recorded QCM-D signal is very similar to the cyclic waveform of the electrochemical signal (i.e., extracellular field potential) of a microelectrode array [ 33 ]. However, we can largely exclude that QCM-D detects changes in ion concentration or the membrane potential as such since the changes in ionic strength of the media due to Ca 2+ -fluxes of the beating CMC are small and the sensor surface is grounded [ 28 ]. In a previous study, the origin of the observed QCM-D signals from cells adhered to the sensor surface where they were undergoing morphological changes was discussed [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…One acoustic technique, the quartz crystal microbalance (QCM) technique, has been successfully applied to studies of attachment and subsequent spreading of cells at the surface of the QCM sensor [ 20 , 21 ], changes in cells exposed to cytomorphic agents [ 21 23 ], exocytotic events in neural cells on the sensor surface [ 24 ], pigment redistribution in melanophores [ 25 ], as well as activation of surface-confined platelets [ 26 ]. Furthermore, QCM has been applied to detect beating of cardiomyocytes, grown in a monolayer on the sensor surface [ 27 ], and to detect spontaneous beating of hPS-CMCs [ 28 ]. These findings show the potential of the QCM technology as a platform for monitoring of CMCs non-invasively, in a label free and real-time manner, aiming not only for the detection of chronotropic characteristics such as, e.g., arrhythmias, but also for properties of the cardiomyocyte contractile machinery, including changes of the QT interval (the time from the beginning of the Q-wave to the end of the T-wave in the electrical cycle of the heart, i.e., the time between the electrical depolarization and repolarization of the ventricles).…”
Section: Introductionmentioning
confidence: 99%
“…Quartz crystal microbalances (QCM) are able to measure small changes to materials adhered on a surface, and have been used to detect the beating of cardiomyocytes. [5][6][7] In these experiments the QCM measurements are taken when there is a thin liquid lm coating the cells, however, when fully submerged in a liquid medium the beating signal becomes difficult to detect as the cells li from the surface. 6 AFM based approaches have also been used to measure cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In these experiments the QCM measurements are taken when there is a thin liquid lm coating the cells, however, when fully submerged in a liquid medium the beating signal becomes difficult to detect as the cells li from the surface. 6 AFM based approaches have also been used to measure cardiomyocytes. Ossola et al were able to combine patch-clamp and AFM techniques to measure the membrane current and forces applied by a contracting cell.…”
Section: Introductionmentioning
confidence: 99%